Outcomes in Patients Treated with Laser Interstitial Thermal Therapy for Primary Brain Cancer and Brain Metastases. (22nd August 2019) - Swartz, Leigh Klaus; Holste, Katherine G.; Kim, Michelle M.; Morikawa, Aki; Heth, Jason
Abstract: Laser interstitial thermal therapy (LITT) is an emerging modality to treat benign and malignant brain lesions. LITT is a minimally invasive method to ablate tissue using laser‐induced tissue heating and serves as both a diagnostic and therapeutic modality for progressive brain lesions. We completed a single‐center retrospective analysis of all patients with progressive brain lesions treated with LITT since its introduction at our center in August of 2015. Twelve patients have been treated for a total of 13 procedures, of which 10 patients had brain metastases and 2 patients had primary malignant gliomas. Biopsies were obtained immediately prior to laser‐induced tissue heating in 10 procedures (76.9%), of which seven biopsies showed treatment‐related changes without viable tumor. After laser ablation, two of three patients previously on steroids were successfully weaned on first attempt. The results of this analysis indicate that LITT is a well‐tolerated procedure enabling some patients to discontinue steroids that may be effective for diagnosing and treating radiation necrosis and tumor progression. Abstract: 激光间质热疗 (LITT) 是一种治疗良性和恶性脑病灶的新型方法?LITT是一种利用激光诱导组织加热来烧蚀组织的微创方法?可作为侵袭性脑病灶的诊断和治疗方法?我们针对自 2015 年 8 月在我们中心引入LITT以来所有接受此项治疗的侵袭性脑病灶患者完成了一项单中心回顾性研究?12 名患者共计接受 13 次手术?其中?10 名患者患有脑转移?2 名患者患有原发性恶性胶质瘤?10 例 (76.9%) 在激光诱导组织加热前即刻行活检?其中 7 例活检显示与治疗相关的改变?无存活肿瘤?在激光烧蚀后?先前使用类固醇治疗的 3 名患者中的 2 名患者第一次成功地停用类固醇?此项分析结果表明?LITT是一种具有良好耐受性的手术?可以让一部分患者停用用于诊断和治疗放射性坏死和肿瘤进展的类固醇? Abstract : Laser interstitial thermal therapy (LITT) is a novel therapy for addressing radiation necrosis and local tumor progression. This article focuses on a possible noninvasive approache for assessing patients to establish an accurate diagnosis and guide optimal management.